Usefulness of the HIV Dementia Scale in Nigerian patients with HIV/AIDS - Olubunmi A Ogunrin; Emeka U Eze; Francis Alika (AOSIS, 2009)
Objective: Information on the cognitive complications of HIV/AIDS from sub-Saharan Africa, where statistics on HIV is alarming, is sparse because of lack of validated cognitive tools. This study assessed the usefulness and predictive validity of the HIV Dementia Scale (HDS) as a screening tool among HIV-positive Nigerian Africans. Design: HIV-positive patients were randomly selected over a period of two months. Setting: The HIV/AIDS outpatient clinic of the University teaching hospital, Benin City, Nigeria. Subjects: Asymptomatic and symptomatic HIV-positive patients were compared with age, sex and level of education-matched controls. Outcome measures: Cognitive performances on the modified HIV Dementia scale. Results: The performances of 160 HIV-positive (comprising 80 asymptomatic and 80 symptomatic) subjects were compared with 80 age, sex and level of education-matched HIV-negative subjects on the HDS. The mean HDS scores (maximum =12) were 10.78±1.18 (comparison subjects), 8.85±1.38 (asymptomatic) and 5.2±1.13 (symptomatic); p